Effectiveness of an Aquatic Play-Based Learning Program On Improving Water Confidence and Fundamental Aquatic Skills in Children Aged 4-7 Years - Komang Ayu Krisna Dewi; I Gede Angga Andika (Jurnal Master Penjas & Olahraga, 2025)
This study examined the effectiveness of an Aquatic Play-Based Learning program in improving water confidence and fundamental aquatic skills among children aged 4-7 years. A quasi-experimental design with a pretest-posttest one-group approach was employed. The participants consisted of 22 beginner-level children. Research instruments included an observational water confidence scale and a fundamental aquatic skills assessment rubric, both validated through expert judgment and reliability testing. Results indicated significant improvements in both water confidence (t = 8.736; p < 0.05) and fundamental aquatic skills (t = 9.284; p < 0.05), with mean increases of 17.13 and 18.09 points respectively. Effect size values of 1.80 and 1.95 were categorized as large effects. These findings suggest that Aquatic Play-Based Learning is highly effective in enhancing both affective and motor domains in early childhood swimming instruction. as an innovative pedagogical model for beginner swimming instruction that is developmentally appropriate, engaging, and safe.